2021
DOI: 10.56196/jta.v11i02.193
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarisme Dalam Budaya Penulisan Karya Tulis Ilmiah

Abstract: Hingga saat ini penulisan karya tulis ilmiah belum terbebas dari prilaku plagiarisme. Plagiarisme merupakan tindakan menyalin atau menggunakan hasil karya milik orang lain tanpa menyebutkan identitas pemiliknya. Plagiarisme merupakan tindakan yang sangat dilarang dalam dunia akademisi. Para pelaku plagiarisme berasal dari kalangan penulis pemula hingga akademisi yang sejatinya paham tentang etika penulisan karya tulis ilmiah. Penelitian ini telah memetakan tantangan dalam penulisan karya tulis ilmiah. Peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…citing other people's writings and publishing them without mentioning the reference source; 2). it was done intentionally or unintentionally (Sinurat et al, 2021) and deliberately carried out by practitioners and academics who understand the ethics of publishing scientific papers, while more are accidentally carried out by novice writers, both students or students who do not know how to make citations or bibliography properly (Sinurat et al, 2021) As found in a class 1A student paper, there are 12 citations written that need to be added to the bibliography. In contrast, three reference sources in the bibliography are not included in the citation or citation.…”
Section: Discussionmentioning
confidence: 99%
“…citing other people's writings and publishing them without mentioning the reference source; 2). it was done intentionally or unintentionally (Sinurat et al, 2021) and deliberately carried out by practitioners and academics who understand the ethics of publishing scientific papers, while more are accidentally carried out by novice writers, both students or students who do not know how to make citations or bibliography properly (Sinurat et al, 2021) As found in a class 1A student paper, there are 12 citations written that need to be added to the bibliography. In contrast, three reference sources in the bibliography are not included in the citation or citation.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sesuai dengan Surat Edaran Dirjen Pendidikan Tinggi No. 152/E/2012 yang dijelaskan bahwa untuk mahasiswa lulusan sarjana wajib menghasilkan publikasi minimal pada jurna nasional [1].…”
Section: Pendahuluanunclassified